2012
DOI: 10.1542/peds.2012-0026
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Pediatric Hospital Mortality After an Intervention to Improve Emergency Care in Lilongwe, Malawi

Abstract: Simple, inexpensive interventions to improve pediatric emergency care at this underresourced hospital in sub-Saharan Africa were associated with decreased hospital mortality rates. The description of this process and the associated results may influence practice and resource allocation strategies in similar clinical environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
86
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 20 publications
12
86
1
1
Order By: Relevance
“…Triage is recognised as being one of the core requirements for the provision of effective emergency care and has been shown to reduce patient mortality. [4] However, in LMICs this strategy is underused, under-resourced and poorly researched.…”
mentioning
confidence: 99%
“…Triage is recognised as being one of the core requirements for the provision of effective emergency care and has been shown to reduce patient mortality. [4] However, in LMICs this strategy is underused, under-resourced and poorly researched.…”
mentioning
confidence: 99%
“…Similarly, effective triage is one of several areas where research and troubleshooting can result in striking improvements for patient outcomes with modest investment. At several centres in Malawi, for example, an improved triage system decreased sepsis mortality from 10-18% per week to 6-8% per week (14,15). Other similar attempts in the USA have improved compliance with sepsis protocols and demonstrated a trend toward mortality benefit (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Specific programmes designed to improve triage processes and sepsis recognition and adherence to goal-directed care have improved outcomes at individual institutions in both resource rich and poor environments (14)(15)(16)(17). At a global level, however, priority areas for research and intervention have not been systematically described.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, there is limited information about pediatric hospital admissions, mortality patterns, and cause mortality in Ethiopian hospitals [6,7]. Previous studies on pediatric hospital mortality in sub-Saharan Africa have demonstrated that deficiencies in pediatric triage, assessment, and emergency treatment at least partially accounts for high inpatient mortality, a large burden of which occurs early during hospitalization [8]. In Ethiopia, one study reported that 33 % of deaths occurred within the first 24 h of admission to the general pediatric ward [6], another reported 34 % within the first 48 h [7], while another reported 100 % of deaths within the first 24 h of admission to the pediatric ICU [9].…”
Section: Introductionmentioning
confidence: 99%